2017
DOI: 10.1292/jvms.17-0374
|View full text |Cite
|
Sign up to set email alerts
|

Application of an enzyme-linked immunosorbent assay for detection of antibodies to <i>Actinobacillus pleuropneumoniae</i> serovar 15 in pig sera

Abstract: An indirect enzyme-linked immunosorbent assay (ELISA) using lipopolysaccharide extract as antigen was evaluated for detection of antibodies to Actinobacillus pleuropneumoniae serovar 15. The serovar 15 ELISA had a higher sensitivity and specificity than latex agglutination test for 63 and 80 sera from pigs experimentally infected and not infected with A. pleuropneumoniae, respectively. When the serovar 15 ELISA was applied to 454 field sera, high rates of seropositivity were found in pigs from farms infected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…With specific genera, pigs fed PO increased the genus Actinobacillus in duodenum and jejunum, and the abundance of Actinobacillus in duodenum and jejunum was negatively correlated with the EE digestibility. Some species within the genera Actinobacillus are putative pathogenic bacteria in association with clinical condition of the respiratory system (Teshima et al, 2017;To et al, 2017). In the present study, the low digestibility of palm oil significantly increased the abundance of Actinobacillus, whereas increased digestibility of palm oil by encapsulation reduced the abundance of Actinobacillus in the small intestine.…”
Section: Fat Types Induced Specific Changes In Microbial Genera and Its Correlations With Nutrients Digestibility Or Growth Performancesupporting
confidence: 46%
“…With specific genera, pigs fed PO increased the genus Actinobacillus in duodenum and jejunum, and the abundance of Actinobacillus in duodenum and jejunum was negatively correlated with the EE digestibility. Some species within the genera Actinobacillus are putative pathogenic bacteria in association with clinical condition of the respiratory system (Teshima et al, 2017;To et al, 2017). In the present study, the low digestibility of palm oil significantly increased the abundance of Actinobacillus, whereas increased digestibility of palm oil by encapsulation reduced the abundance of Actinobacillus in the small intestine.…”
Section: Fat Types Induced Specific Changes In Microbial Genera and Its Correlations With Nutrients Digestibility Or Growth Performancesupporting
confidence: 46%
“…However, most commercial ELISAs have been developed for serotype determination of A. pleuropneumoniae and cannot be easily applied to measure Apx-specific immune responses when evaluating the efficiency of Apx toxins-based subunit vaccines [112425]. In addition, experimental ELISAs reported in previous studies are also still difficult to differentiate levels of immunization against respective Apx toxin antigens [32629]. This problem is believed to be due to cross-reactivity among ApxI, ApxII, and ApxIII as a result of their high homology [21272829], which was also observed in homology analysis conducted in the present study (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, these approaches are not suitable for evaluation of the immune responses to each Apx toxin. Enzyme-linked immunosorbent assay (ELISA) using purified recombinant protein antigens is more sensitive than other methods and is able to determine antibody titers against each antigen [5242526]. Thus, ELISA methods have an advantage in evaluating vaccine efficiency for the development of subunit vaccines of A. pleuropneumoniae [3192026].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported several techniques for the identification of Actinobacillus pleuropneumoniae such as ribotyping and restriction analysis of PCR(PCR-REA) (Jaglic et al, 2004), multiple PCR based on the omlA gene (Angen et al, 2008) and enzyme-linked immunosorbent assay (ELISA) using the recombinant ApxIA, ApxIIA, ApxIIIA, ApxIVA proteins and lipopolysaccharide (Shin et al, 2011;Sassu et al, 2017;Teshima et al, 2017). Tremblay et al (2017) developed an ApxIV probe which could specifically detect APP in the swine lung tissue.…”
Section: Discussionmentioning
confidence: 99%